Penyusunan APBN dalam Konsep Maqashid Syariah APBN dalam Perspektif Pemenuhan 5 Kebutuhan Dasar Perkembangan Ekonomi Islam dan Kehadiran Perbankan Syariah - Yetti, Febri Delmi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The preparation of the State Budget (APBN) is one of the vital instruments in achieving the goals of equitable economic development and public welfare. From an Islamic economic perspective, the APBN must be based on the principles of maqashid sharia which prioritize the welfare of the people. The five basic needs according to maqashid sharia—maintaining religion, soul, mind, descendants, and property—must be the basis for preparing the state budget. This study aims to analyze how the preparation of the APBN can be in line with maqashid sharia, as well as explore the role of Islamic economics and Islamic banking in supporting a more inclusive and equitable fiscal policy. Using a qualitative approach, this study analyzes related literature and fiscal policy in Indonesia, as well as examples of the application of sharia principles in state financial management exemplified by Umar bin Khattab. The results of the study are expected to provide recommendations for the government in preparing a more effective APBN in improving public welfare and avoiding economic crises.